A school-based intervention programme to prevent anxiety and depression among Chinese children during the COVID-19 pandemic - Jiameng Li; Therese Hesketh (BMC, 2024)
Abstract Background Child and adolescent mental health is a major public health concern worldwide. The development of children's social and emotional skills helps to improve mental health and wellbeing, and prevent anxiety and depression. The school-based social emotional learning (SEL) programmes have proved effective in a number of countries. But in Mainland China, there has been no empirical research of the effectiveness on children's mental health. The study conducted a SEL programme in China during the COVID-19 pandemic and aimed to determine whether: (1) a SEL programme can reduce anxiety and depression, (2) the intervention effect is influenced by sociodemographic characteristics, (3) the programme effects change children's emotion management and communication. Methods Participants were 230 children aged 8-12 years in the intervention school and 325 in the control school in two poor villages in central China. The study was a quasi-experimental trial, comprising 16 weekly 90-minute sessions. It used a mixed-methods design, with a quantitative survey administered at baseline, post-intervention, and 5-month follow-up, and qualitative interviews. Linear mixed effects regression modeling was used to analyse the intervention effectiveness, linear models were conducted to examine the moderation effect of sociodemographic variables, and the inductive thematic analysis approach was used for interview data. Results The intervention had no significant effect on anxiety or depression, except that intervention school children who lived with neither parent (left behind children) reported lower depression scores than control school at post-intervention and 5-month follow-up. Qualitative interviews showed after intervention children were more able to control tempers and better communicated their thoughts and feelings, improving their relationships with family and friends. Conclusions The programme was cheap, easy to implement, and warmly welcomed by children, schools and caregivers, suggesting it was feasible and potentially sustainable. More research is needed on the adaptation of the SEL programme in the Chinese context.